AN UNIQUE EXAMPLE OF THE TOMB FROM ANATOLIA: TARSUS DUATEPE TOMB - H. Sibel ÜNALAN ÖZDEMİR (Fırat University, 2019)
Tarsus, one of the historically oldest and largest towns of the city of Mersin, has almost always been an important center in the historical process due to its geographical location. It is thanks to the archeological excavations carried out at Tarsus that its occupation is deduced to date back to the Neolithic period. Going much further back in history palette, Tarsus has been the setting for many civilizations. The knowledge of the existence of many architectural buildings belonging to Turco-Islamic period is obtained from both travelogues, historical sources and documents, and the publications on Tarsus as well. However, there is an architectural building which there is no information is given in these sources and documents, except for one article in which its name, location are given and is shortly introduced by including its facade drawings, and this building is our research subject. Located in the yard of Hasan Karamehmet Elementary School, on the western skirts of Gözlukule Mound in the south of Tarsus, the tomb which has been put under protection by the efforts of the excavation team carrying out Gözlükule excavations within the boundaries of the archeological site is publicly known as Duatepe Tomb. Although it looks like an ordinary tomb with its construction material, workmanship and appearance, it is a significant example having some interesting features both for history of architecture and Tarsus. The masonry structure, which has a square plan and is covered by cloistered vault, is also surrounded by a square planned periphery wall. The top of the corridor, which is created around the square planned structure by this periphery wall, is kept open. No ornament is located in the extremely simple structure. This tomb is unique in terms of architectural feature and plan design ever built in Anatolia, and is a vital example for the researchers who will study on funerary monuments. Accordingly, the aim of this study is to introduce the unknown tomb with statistical drawings and photographs, on which there have been no scientific publications in the field of Art History; and ultimately to clarify the place and importance of it in the Turkish Architecture and in the history of Tarsus.